Vulnerability Analysis of Macroeconomic Indicators for Early Detection of Currency Crisis: Case Study of Indonesian Economy on 1991–2019 - HADI SUTRISNO, 099913380 M (World Scientific Publishing Co. Pte Ltd, 2021)
The purpose of this study is to detect the currency crisis in Indonesia by exploring the vulnerability of macroeconomic variables. The Exchange Market Pressure Index was used to determine the crisis period by modeling the threshold value. Early indicators were determined using the signal analysis approach; therefore, the vulnerability level of each macroeconomic variable is known and used to determine the leading indicators. The result showed that the Signal Analysis and Herrera–Garcia approaches are the best detection models. Furthermore, it was concluded that the Signal Analysis approach was better in detecting crises compared to the Herrera–Garcia approach.